When Left is One and Right is Double: An Experimental Investigation of Visual Allesthesia after Right Parietal Damage - Denise Baumeler; Sabine Born; Nicolas Burra; Radek Ptak (Vision, 2020)
Illusory visual phenomena, such as palinopsia, polyopsia or allesthesia, are rare manifestations of posterior cortical damage. Symptoms are characterized by illusory perceptions, ranging from isolated stationary objects to scenes and moving persons. Such illusions may appear while the original object is still in view, or become manifest with a delay and last for minutes, hours or even days. Some authors have suggested a disinhibited cortical response underlying visual illusions, but experimental studies supporting this hypothesis are lacking. Here, we examined a rare patient who after focal right parietal injury consistently reported a second stimulus on the left when briefly shown a target in his right hemifield. The patient perceived the illusory stimulus as less intense, and therefore concluded that it must have a different shape than the original stimulus. A masking experiment revealed that the frequency of the illusion was inversely related to the visibility of the original stimulus, suggesting that it depended on early, feedforward visual processing. We propose that illusory perceptions reflect the interplay of two physiological processes: a fast and automatic activation of contralateral, homotopic visual cortex after unilateral stimulation, and the lack of top-down inhibition following damage to the posterior parietal cortex.